Perception of COVID-19 Vaccination Based on Health Belief Model and the Acceptance of COVID-19 Booster Vaccination - Risma Arlyani Dewi; Jon Hafan Sutawardana; Ana Nistiandani (Nurse Media Journal of Nursing, 2023)
Background: The COVID-19 booster vaccination proposes a spike in cases due to new infection variants. According to the Health Belief Model (HBM), vaccination acceptance is a health change behavior measured by perception. However, more information is needed about the relationship between public perception and future acceptance of the COVID-19 booster vaccination.Purpose: This research aimed to analyze the relationship between the perception of COVID-19 vaccination based on the HBM and the acceptance of COVID-19 booster vaccination.Methods: The research used observational analytics design with a cross-sectional approach conducted at the community of a public health center in Jember Regency, Indonesia. Purposive sampling was used to recruit 387 respondents. The inclusion criteria were people aged >18 who had received a complete primary vaccination. The research instruments consisted of some questionnaires: respondent characteristics, perceptions of COVID-19 vaccination based on the HBM, and the acceptance of COVID-19 booster vaccination. Data were analyzed using Chi-square and a logistic regression test.Results: The results showed that most respondents accepted the COVID-19 booster vaccine (67.4%). There was a significant relationship between perception’s subscales of COVID-19 vaccination, such as perceived susceptibility (p=0.001), perceived severity (p=0.001), perceived benefits (p=0.001), perceived barriers (p=0.001), cues to action (p=0.001) and the acceptance of the COVID-19 booster vaccination. Cues to action were the most dominant factor related to the acceptance of the COVID-19 booster vaccination (OR=5.265; 95%CI=3.073-9.022; p<0.001).Conclusion: Positive perceptions of all HBM subscales, which showed a good perception in the community, indicated the high acceptance of the COVID-19 booster vaccine. For clinical practice, this research can be developed by surveying patients who have comorbidities.